(untitled) (GUB Journal of Science and Engineering, 2021)
The study was conducted to analyze the groundwater potential zones in the Eastern part of Kushtia district. Secondary data collected from Bangladesh Agriculture Development Board Corporation (BADC) and borehole data of 119 locations have been processed, analyzed and interpreted for studying the hydrogeological properties. The sub-surface groundwater-bearing sequence of the area up to the depth of 97 m have been classified into two main hydrostratigraphic units- aquitard and aquifer, consisting of clay-silt-sand and sands of different granular respectively. The 18-30 m thick aquitard is covering a major part of the study area. The thickness of main aquifers is varying from 0.9-30 m and 27-67 m consisting of fine-medium to coarse sand. The yield potential index is 1.3-13.0. However, from the obtained results, it can be concluded that the area is suitable for groundwater potentiality. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 7, Dec 2020 P 36-41